Endogenous retinoic acid activity in principal cells and intercalated cells of mouse collecting duct system. - Yuen Fei Wong (Public Library of Science (PLoS), 2011)
Background Retinoic acid is the bioactive derivative of vitamin A, which plays an indispensible role in kidney development by activating retinoic acid receptors. Although the location, concentration and roles of endogenous retinoic acid in post-natal kidneys are poorly defined, there is accumulating evidence linking post-natal vitamin A deficiency to impaired renal concentrating and acidifying capacity associated with increased susceptibility to urolithiasis, renal inflammation and scarring. The aim of this study is to examine the presence and the detailed localization of endogenous retinoic acid activity in neonatal, young and adult mouse kidneys, to establish a fundamental ground for further research into potential target genes, as well as physiological and pathophysiological roles of endogenous retinoic acid in the post-natal kidneys. Methodology/principal findings RARE-hsp68-lacZ transgenic mice were employed as a reporter for endogenous retinoic acid activity that was determined by X-gal assay and immunostaining of the reporter gene product, β-galactosidase. Double immunostaining was performed for β-galactosidase and markers of kidney tubules to localize retinoic acid activity. Distinct pattern of retinoic acid activity was observed in kidneys, which is higher in neonatal and 1- to 3-week-old mice than that in 5- and 8-week-old mice. The activity was present specifically in the principal cells and the intercalated cells of the collecting duct system in all age groups, but was absent from the glomeruli, proximal tubules, thin limbs of Henle's loop and distal tubules. Conclusions/significance Endogenous retinoic acid activity exists in principal cells and intercalated cells of the mouse collecting duct system after birth and persists into adulthood. This observation provides novel insights into potential roles for endogenous retinoic acid beyond nephrogenesis and warrants further studies to investigate target genes and functions of endogenous retinoic acid in the kidney after birth, particularly in the collecting duct system.